Personality Of King George VI In Tom Hooper's The King's Speech Movie (2010): A Psychoanalytic Approach - Pusfitarini, Retno Dewi; , Drs. Abdillah Nugroho, M. Hum; , Nur Hidayat, S. Pd (2013)
Her study investigates personality of King George VI reflected in The King's Speech movie viewed from psychoanalytic approach. Her research is aimed to analyze personality of King George VI viewed in character of King George VI based on psychoanalytic perspective and analyze the movie based on its structural elements. In achieving the objectives, the researcher uses descriptive qualitative method as the type of the research. The object of her study is The King's Speech movie by Tom Hooper. The data sources are the primary data and secondary data. The primary data are the movie itself and the secondary data are the other data which have relationship with the study, such as some biography of the author, the books and other relevant information. In collecting the data, the researcher uses documentation method and the technique of the data analysis is descriptive analysis. Based on the psychoanalytic analysis, in The King's Speech, Tom Hooper describes how the personality of King George VI is one of causes the story become interesting, because he has an interesting personality. He is a kind person who can give influence for the audiences because King George VI has good personality, even though he has stammer, but he is very responsible for his duty. Structure of King George VI's personality shows interesting conflict between id, ego, and superego. It can be seen from King George VI has done in this movie, such as when King George VI's superego pressures id to be a king although he knows that he never wishes to be king of England. He knows the limitations he has. He has stammer but he always strives to recover his stammer.